Deepening decentralization in Zambia: Political economy constraints and opportunities for reform - Resnick, Danielle; Siame, Gilbert; Mulambia, Peter; Ndhlovu, Dorothy; Shicilenge, Beverly; Sivasubramanian, Bhavna (International Food Policy Research Institute, 2019)
Since the early 2000s, decentralization has been espoused as a major policy goal of successive Zambian governments. With the passing of the 2019 Local Government Act, a greater understanding is needed of how decentralization has progressed thus far in Zambia and how political economy dynamics have constrained the process. As such, a survey was conducted with 153 bureaucrats across 16 councils in four Zambian provinces, complemented by interviews with elected ward councilors. Three key findings emerge. First, the organizational setting in which councils operate undermines the continuity of service provision. In particular, transfers of staff by the Local Government Service Commission (LGSC), partially driven by the growth in the number of councils in recent years, increases pressure on the wage bill of local authorities, creates uncertainty for civil servants, and undermines institutional memory. Second, the unwillingness to cede genuine autonomy to local councils by the Ministry of Local Government (MLG) repeatedly emerged. A perception of low levels of consultation with council bureaucrats and elected councilors, especially when statutory instruments are issued, reinforce that accountability remains upwards to the MLG rather than downwards to citizens. Third, within the councils, there is a mismatch in incentives between the bureaucrats and politicians that can undermine policy implementation; while the former respect authority and attention to procedures, the latter are focused on constituents’ priorities and may bypass formal procedures to deliver to their voters. Based on interviews with market committees and solid waste companies, these dynamics have negative externalities on citizen perceptions and service provision in urban areas. As one of the few analyses conducted with local bureaucrats to assess their experiences with decentralization, the study aims to advance both policy and scholarship about the political economy dynamics surrounding efforts to strengthen subnational capabilities in developing countries.